Early Recognition of Anomalous Origin of Right Pulmonary Artery From The Ascending Aorta with Minimal Limited Resources - Sukmapermata, Bunga; Yanti, Ni Putu Veny Kartika; Gunawijaya, Eka (Jurnal Indonesia Sosial Sains, 2025)
The anomalous origin of the right pulmonary artery (AORPA) is a rare congenital heart defect with a poor prognosis if not surgically corrected. Atypical symptoms often lead to underdiagnosis and delayed treatment, necessitating timely and accurate examination. The utility of diagnostic tools, especially in resource-limited settings, remains a subject of debate. This research aims to assess the effectiveness of echocardiography and cardiac CT in detecting AORPA in children suspected of having congenital heart disease (CHD), compared to catheter angiography and/or surgery. A case report of a male term newborn presenting with respiratory distress and heart failure was presented. Initial diagnosis was made via echocardiography, which was later confirmed by computed tomography angiography (CTA). A literature search was conducted using PubMed, Google Scholar, and ScienceDirect with keywords such as "anomalous origin of right pulmonary artery," "ascending aorta," "children," "echocardiography," and "cardiac CT". Two relevant articles were critically appraised. The case demonstrated that transthoracic echocardiography (TTE) provided a timely diagnosis of AORPA at 11 days old, even when MDCT was delayed due to the patient's critical condition. While MDCT is superior for detailed anatomical features, TTE proved valuable as an initial diagnostic modality in a resource-limited area. Literature review showed TTE diagnostic accuracy at 88.9%, and MDCT with high sensitivity and specificity for pulmonary arterial anomalies. Despite diagnosis, the patient deteriorated and died without surgical repair. Early diagnosis and prompt surgical correction are essential for improved outcomes.